A Dichoptic Optokinetic Nystagmus Paradigm for Interocular Suppression Quantification in Intermittent Exotropia - Cai, Xiaoxiao; Chen, Zidong; Liu, Yanping; Deng, Daming; Yu, Minbin (Frontiers in Neuroscience, 2021)
Purposes: To investigate the effectiveness of a dichoptic optokinetic nystagmus (dOKN) test to objectively quantify interocular suppression in intermittent exotropia (IXT) patients during the states of orthotropia and exodeviation. Methods: The OKN motion in subjects (15 controls and 59 IXT subjects) who viewed dichoptic oppositely moving gratings with different contrast ratios was monitored and recorded by an eye tracker. Interocular suppression in control subjects was induced using neutral density (ND) filters. The OKN direction ratios were fitted to examine the changes of interocular suppression in subjects under different viewing states. Two established interocular suppression tests (phase and motion) were conducted for a comparative study. Results: The dOKN test, which requires a minimal response from subjects, could accurately quantify the interocular suppression in both IXT and control subjects, which is in line with the established interocular suppression tests. Overall, although comparative, the strength of interocular suppression detected by the dOKN test (0.171±0.088) were stronger than those of the phase (0.293±0.081) and the motion tests (0.212±0.068) in the control subjects with 1.5 ND filters. In IXT patients, when their eyes kept aligned, the dOKN test (0.58±0.09) measured deeper visual suppression compared with the phase (0.73±0.17) or the motion test (0.65±0.14). Interestingly, strong interocular suppression (dOKN: 0.15±0.12) was observed in IXT subjects during the periods of exodeviation, irrespective of their binocular visual function as measured by synoptophore. Conclusion: The dOKN test provides efficient and objective quantification of interocular suppression in IXT, and demonstrates how it fluctuates under different eye positions.